(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Cooperatives were the first formal institution to be conceived and developed to purvey credit to rural India. Indian Economy is largely dependent upon agriculture as majority of its population is employed in it. In India, there are 20 State Co-operative agricultural and rural development banks at apex level and 697 Primary Co operative agricultural and rural development banks at base level are playing an important role in meeting credit requirement of rural population in India. The present study was formulated with the specific objectives to analyze the growth and performance of Land Development Banks in India in reference to number of banks, owned funds, deposits, borrowings, loans and advances, total assets, profits/losses, non performing assets, ratio of non performing assets to loans outstanding and ratio of recovery to demand. The present study is based on secondary data and it has been collected from the publication of NABARD and RBI that is, Report on trend and Progress of banking in India, 2001-02 to 2012– 2012. The data has been collected for twelve years from 2001-02 to 2011-12. The progress has been analysed by selecting statistical tools like, mean, standard deviation, coefficient of variation and exponential growth rate, trend coefficient, future predication in absolute and relative terms. From the analysis, it has been observed that during the study period the performance of land development banks in India was not satisfactory, State banks must take necessary steps to improve their performance. The India state co-operative agricultural and rural development banks are apex banks and they can control and improve the performance of Primary Co operative agricultural and rural development banks under their vast umbrella.